Peran media sosial, citra merek, dan persepsi harga dalam meningkatkan minat beli Konsumen Produk Eiger di Kota Semarang - Wiranto, Hardiy; Amron, Amron (Journal of Management and Digital Business, 2024)
The development of outdoor equipment products has recently experienced very rapid development. This condition can be seen from the increasing competition of similar products, such as imported and domestic products. Outdoor equipment products on the market affect a person's buying interest because of their price and quality. This study aimed to determine the effect of brand image, social media, and price perception on buying interest in Eiger Adventure products in Semarang City. This research method uses quantitative methods, and the population is consumers who have purchased Eiger Adventure products in Semarang City. The sample consisted of 100 respondents selected using purposive sampling, with the condition that consumers were 17 to 50 years old. The data collection technique used was a questionnaire. The data analysis used was multiple linear regression. The results of this study indicate that social media and price perception affect buying interest, while the brand image does not affect buying interest in Eiger products.